Great world religions Buddhism - Eckel, Malcolm David 1946-. (Chantilly, Va. Teaching Co., 2003)
Consists of twelve 30-min. lectures that provide an overview of Buddhism. Describes how Buddhism challenges some of the most important Western ideas about God, human life, and the self. Covers Buddha's life, explains his teachings and explores the lives of well-known Buddhists such as the Dalai Lama.
disc 1. Buddhism as a world religion. Life of the Buddha. All is suffering. Path to Nirvana. Buddhist community. Mahayana Buddhism, the bodhisattva ideal -- disc 2. Celestial Buddhas and bodhisattvas. Emptiness. Theravada Buddhism in Southeast Asia. Buddhism in Tibet. Buddhism in China. Buddhism in Japan.
"Library edition"--Container.
"Course Number 6105."
DVD, region 1.
Keywords: Buddhism